Hand rehabilitation programmes for second to fifth metacarpal fractures: A systematic literature review - Monique M. Keller; Roline Barnes; Corlia Brandt; Lauren M. Hepworth (AOSIS, 2021)
Background: Metacarpal fractures, one of the most prevalent upper limb fractures, account for 10% of all bony injuries. Objective: Our systematic review aimed to review, appraise and collate available evidence on hand rehabilitation programmes for the management of second to fifth metacarpal fractures in an adult human population after conservative and surgical management. Since 2008, no review on a similar topic has been performed, thus informing clinical practice for physiotherapists and occupational therapists. Methods: Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) principles guided the reporting. Experimental, quasi-experimental, cohort and case-control studies between January 2008 and September 2018 were included. Searches were conducted on Medline, Academic Search Ultimate, CINAHL, CAB Abstracts, Health Source - Consumer Edition, Health Source: Nursing/Academic Edition, SPORTDiscus, Africa-Wide Information and MasterFILE Premier, Web-of-Science and Scopus. Screening, selection, appraisal and data extraction were independently performed by two reviewers. No meta-analysis was performed. Results: A total of 1015 sources were identified, 525 duplicates removed and 514 excluded. Three articles were included in the final data extraction: one randomised controlled trial (RCT) and two observational studies. Conclusion: Limited evidence is available that a well-designed, well-implemented home-based exercise programme results in statistically significant improved hand function (p ˂ 0.0001) and digital total active motion (TAM) (p = 0.013) compared with traditional physiotherapy (PT) post-surgically. Clinical implications: Our study contributes to the knowledge base of hand rehabilitation after an individual sustained a second to fifth metacarpal fracture. The authors identified a gap where future studies should further investigate the effect of hand rehabilitation after conservative and surgical management.